2003
DOI: 10.1071/ch03027
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity in the Syntheses of Enantiopure 2-Benzopyrans through Intramolecular Cyclization of Tethered Lactaldehydes. Conformations of the Products

Abstract: Using titanium tetraisopropoxide, the enantiopure tethered lactaldehyde (α′ S,2S)-2-(3′-hydroxy-α′-methyl-benzyloxy)propanal (6) is cyclized with complete regio- and diastereoselectivity ortho to the phenolic hydroxyl group to give (1S,3S,4R)-3,4-dihydro-1,3-dimethyl-2-benzopyran-4,5-diol (7). Similar cyclization of the epimeric (α′ R,2S)-lactaldehyde (25) yields solely the corresponding (1R,3S,4R)-4,5-diol (34). The 4,5-diacetate (26), but not (35), undergoes conformational inversion of the heterocyclic ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The established protocol for synthesizing 1 from alcohol 3 via (−)-triptonide ( 2 ), a congener recently showing promise as a reversible nonhormonal male contraceptive agent, inspired us to conceive a novel approach toward 3 or alike structures (Figure b). To this end, an aldol-like cyclization of aldehyde 4 was devised to forge the C7 stereogenic center . We envisaged that the C5–C10 bond in 4 could be constructed through a metal-catalyzed hydrogen atom transfer (MHAT)-initiated reductive cyclization process, whereas C3–C4 olefin was strategically saturated to secure the correct stereogenic centers of C5 and C10, tracing back to aldehyde 5 as a key precursor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The established protocol for synthesizing 1 from alcohol 3 via (−)-triptonide ( 2 ), a congener recently showing promise as a reversible nonhormonal male contraceptive agent, inspired us to conceive a novel approach toward 3 or alike structures (Figure b). To this end, an aldol-like cyclization of aldehyde 4 was devised to forge the C7 stereogenic center . We envisaged that the C5–C10 bond in 4 could be constructed through a metal-catalyzed hydrogen atom transfer (MHAT)-initiated reductive cyclization process, whereas C3–C4 olefin was strategically saturated to secure the correct stereogenic centers of C5 and C10, tracing back to aldehyde 5 as a key precursor.…”
Section: Resultsmentioning
confidence: 99%
“…Even though 14 could be converted to 4 to finish the synthesis (Scheme S1), we decided to introduce the C3–C4 olefin at a later stage of synthesis by considering the step- and redox-economy . Consequently, deprotection of the phenol silyl ether in 14 by NEt 3 ·3HF followed by the treatment with Ti­(OiPr) 4 successfully materialized the aldol-type cyclization, and subsequent addition of aqueous solution of NaIO 4 into the same flask direct afforded 16 as the final isolable product in 55% yield as a single diastereomer. , Epoxidation of C9–C11 olefin afforded 17 , the crude product of which was further oxidized to introduce the C12–C13 epoxide in a diastereoselective manner . The epimerization of the C3 stereogenic center by DBU before the treatment of H 2 O 2 /K 2 CO 3 was essential to prevent the hydrolysis of lactone during the scale-up, providing 18 in 53% yield over two steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study 24, 25 we showed that the phenolic lactaldehyde 49 unsubstituted para to the phenolic hydroxyl group cyclised with complete diastereoselectivity to give the cis-1,3dimethylbenzopyran-4,5-diol 42 in good yield, none of the epimeric C-4 diol 47 being formed, whereas an earlier study 9 showed that the corresponding methoxy lactaldehyde 50 cyclised with lower diastereoselectivity to afford the pair of C-4 epimeric cis-1,3-dimethylbenzopyran-4,5-diols 43 and 48 in a ratio of 75 : 25, with the pseudoequatorial alcohol still predominating. In the present study the diastereoselectivity is even less, with cyclisation of the corresponding brominated benzyloxy derivative yielding the two C-4 epimeric cis-1,3-dimethylbenzopyrans 39 and 44 in a ratio of 62 : 38.…”
Section: Syntheses Of Benzopyranquinones 12 and 58-64mentioning
confidence: 92%